Interaksionisme Simbolik dan Prakmatis - Efendi, Erwan; Fadila, Farah; Tariq, Khairi; Pratama, Teguh; Azmi, Wardatul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The basic idea of symbolic interaction theory states that the emblem or symbol of culture are learned thourgh interaction, people give meaning to everything that will control their attitude and behavior. To understand the intraction of symbolic (symbolic interactionism) is a way of thingking about the mind (mind), self (self) and society (society). By using sociology as a foundation, as well as teaching that when human interact with each other, they share the meaning for a certain period and for a specific action. George Herbert Mead is a figure who is seen as symbolic interaction builders understand this. He taught tha the meaning comes as a result of inetarction between people, both verbally and nonverbally. Through the actions and responses that occur, we give meaning to the words or actions, and therefore we can also understand an even in certain ways too, because people are assumend to a rise from interrelated conversations between individuals.